Associate Professor Dr. Azrina produces hydrocarbon fuel through photocatalytic CO2 conversion using nanoparticles - Safriza, Baharuddin; Nur Hartini, Mohd Hatta (2021)
GAMBANG, 7 June 2021 - A research titled ‘Nanoparticles for CO2 Conversion’ conducted by Associate Professor Dr. Azrina Abdul Aziz, 35, focuses on novel nanocomposite photocatalyst synthesis by implementing electrochemical anodisation, electrochemical deposition, and immersion method.